HuR-dependent expression of Wisp1 is necessary for TGFβ-induced cardiac myofibroblast activity. (January 2023) - Green, Lisa C.; Slone, Samuel; Anthony, Sarah R.; Guarnieri, Adrienne R.; Parkins, Sharon; Shearer, Shannon M.; Nieman, Michelle L.; Roy, Sudeshna; Aube, Jeffrey; Wu, Xiaoqing; Xu, Liang; Kanisicak, Onur; et al.
Abstract: Cardiac fibrosis is regulated by the activation and phenotypic switching of quiescent cardiac fibroblasts to active myofibroblasts, which have extracellular matrix (ECM) remodeling and contractile functions which play a central role in cardiac remodeling in response to injury. Here, we show that expression and activity of the RNA binding protein HuR is increased in cardiac fibroblasts upon transformation to an active myofibroblast. Pharmacological inhibition of HuR significantly blunts the TGFβ-dependent increase in ECM remodeling genes, total collagen secretion, in vitro scratch closure, and collagen gel contraction in isolated primary cardiac fibroblasts, suggesting a suppression of TGFβ-induced myofibroblast activation upon HuR inhibition. We identified twenty-four mRNA transcripts that were enriched for HuR binding following TGFβ treatment via photoactivatable ribonucleoside-enhanced crosslinking and immunoprecipitation (PAR-CLIP). Eleven of these HuR-bound mRNAs also showed significant co-expression correlation with HuR, αSMA, and periostin in primary fibroblasts isolated from the ischemic-zone of infarcted mouse hearts. Of these, WNT1-inducible signaling pathway protein-1 (Wisp1; Ccn4 ), was the most significantly associated with HuR expression in fibroblasts. Accordingly, we found Wisp1 expression to be increased in cardiac fibroblasts isolated from the ischemic-zone of mouse hearts following ischemia/reperfusion, and confirmed Wisp1 expression to be HuR-dependent in isolated fibroblasts. Finally, addition of exogenous recombinant Wisp1 partially rescued myofibroblast-induced collagen gel contraction following HuR inhibition, demonstrating that HuR-dependent Wisp1 expression plays a functional role in HuR-dependent MF activity downstream of TGFβ. In conclusion, HuR activity is necessary for the functional activation of primary cardiac fibroblasts in response to TGFβ, in part through post-transcriptional regulation of Wisp1. Highlights: HuR is highly expressed in cardiac fibroblasts and its expression strongly correlates with markers of active myofibroblasts HuR inhibition reduces migration, contraction, and ECM production activity of cardiac fibroblasts Expression of the secreted matricellular protein, Wisp1, is increased in a HuR-dependent manner following TGFβ treatment Recombinant Wisp1 rescues myofibroblast contractile function following HuR inhibition HuR-dependent expression of Wisp1 is necessary for myofibroblast activation